Wave breaking analysis for the periodic rotation-two-component Camassa–Holm system. (October 2019) - Liu, Jingjing; Pucci, Patrizia; Zhang, Qihu
Abstract: In this paper we study the blow-up phenomenon of the initial boundary value problem for the periodic rotation-two-component Camassa–Holm (R2CH) system. The results include a precise blow-up criterion, when σ > 0, and two new blow-up statements and the exact blow-up rate for strong solutions of the system.